Difference in Efficacy of Antihypertensive Given in Morning vs Evening - Fatima, Syeda Faryal; Ahmad, Faisal; Abubakar, Saadia; Batool, Nida; Ahmad, Noman; Anwar, M. Wasiq (Indus Journal of Bioscience Research, 2025)
Background: The long-term antihypertensive drugs of 24-hour stable blood pressure can control the large fluctuation of morning blood pressure and reduce the rise of morning peak blood pressure caused by failure to take medicine on time or missing. Objective: To determine the difference in efficacy of antihypertensive given in morning vs evening, at a tertiary care hospital, Karachi. Material and Methods: A randomized controlled trial was conducted at Liaquat National Hospital & Medical College, Karachi from March 2024 to Sep 2024. 200 hypertensive patients were randomly assigned to Morning (Group-A) or Evening/Night (Group-B) medication groups. For diagnosing and evaluating hypertension, ABPM was performed using validated devices that recorded systolic and diastolic blood pressure at regular intervals over 24 hours. Data were analyzed using SPSS, applying appropriate statistical tests (parametric and non-parametric) to compare outcomes. A p-value ≤0.05 was considered statistically significant. Results: Group-A had 62% males and 38% females, while Group-B had 66% males and 34% females. Hypertension duration was significantly longer in Group-B (16.32±8.10 months vs. 10.64±5.82 months, p<0.001). Blood pressure reductions favored evening administration, with post-systolic and post-diastolic blood pressures decreasing significantly in Group-B (135.40±9.00 mmHg, 73.81±6.78 mmHg) compared to Group-A (142.41±12.93 mmHg, 82.39±6.19 mmHg, p<0.001). The main outcome revealed superior efficacy in the evening group, where 87% reported effectiveness compared to 53% in the morning group. Conclusion: Our study results demonstrate that evening administration of antihypertensive medications significantly improves efficacy compared to morning dosing, with greater reductions in systolic and diastolic blood pressures and higher effectiveness rate.